Post-truth conspiracism and the pseudo-public sphere - de Zeeuw, Daniël (Frontiers in Communication, 2024)
Rather than seeking to recuperate the ideal of a digital public sphere or lament its demise with the rise of social media platforms, in this paper I seek to identify the dangers of precisely this insistence to imagine the Internet as a public sphere. It is this curious insistence and persistence that, I claim, may feed into precisely those post-truth media dynamics such critical accounts worry about and rally against. The success of viral conspiracy narratives like Pizzagate and QAnon, as well as other forms of mis-and disinformation, hinges not (only) on the absence or distortion of a healthy democratic public sphere, as is typically assumed, but (also) on its persistence as an imaginary in an environment that obeys an altogether different set of logics, namely that of 'communicative capitalism' and 'information warfare'. Whereas the former has drawn most critical attention in connection to current post-truth dynamics (e.g. the effects of targeted advertising and the role of algorithms in creating polarizing echo chambers and filter bubbles), I will instead focus on the latter. The unique problem and 'cunning' of what I refer to as 'post-truth conspiracism' is that it draws from idea(l)s of digital publicness to establish its own epistemic legitimacy, as well as derive its unique powers of persuasion, while also mobilizing the full tactical arsenal of information warfare in a global attention economy. The resulting weaponization of digital public sphere imaginaries thereby complicates any attempt to recuperate the idea(l) of a digital public sphere as a solution to a 'polluted' information environment.